Temporary Mobilities Regenerating Rural Places. Case Studies from Northern and Eastern Finland - Pitkänen, Kati; Sireni, Maarit; Rannikko, Pertti; Tuulentie, Seija; Hiltunen, Mervi J. (Rural Development Institute, Brandon University, 2017)
Sparsely populated northern resource communities have been marked by flows of out-migration and an aging population. However, rural places are also becoming the locus of a range of leisure and work related mobilities. The aim of the paper is to identify different forms of rural mobilities and analyse their economic and socio-cultural importance for peripheral development. We introduce a framework of temporary mobilities to study the range of seasonal and temporary movements and mobile groups. The framework is applied to a forestry dependent community in eastern Finland, and a second home community in Finnish Lapland. These northern communities have traditionally been dependent on the use of natural resources. Our analysis shows that during past decades however, their development has become increasingly defined by tourists, recreationists, second home owners and seasonal workers. Our findings highlight the importance of fixity, stopping and staying when evaluating the consequences and potentials of mobilities for rural development.
Keywords: rural; resource communities; temporary mobilities; Finland; sparsely populated areas; communities